Ischemic stroke and melodic intonation therapy: a case report - Palacios Lenis, Jennifer; Moncaleano Obregón , Paula Andrea; Córdoba Hoyos , Vanessa; Larrahondo Gómez, María; Guzmán Sánchez , Pilar Andrea (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
Introduction: Brain alterations in adults bring with them clinical manifestations that compromise the functionality of human beings in different spheres, one of them is language, which can affect understanding and / or expression; this pathology is known as aphasia. Objective: To determine the effectiveness of TEM in the symptom of agrammatism Clinical case: A 55-year-old male, with right-handed laterality, with a history of brain damage and presented aphasic symptoms, without prior treatment for their symptoms. oral language difficulties, who undergoes 12 intervention sessions with a frequency of three times a week. Conclusion: The results reveal an increase in oral production in conversational and descriptive speech in information content, fluency, and sentence length.